BENTUK DAN JENIS KALIMAT BAHASA INDONESIA ANAK USIA 3-4 TAHUN DI PLAY GROUP LERENG HIJAU KABUPATEN JENEPONTO - Liah, Nur; Darwis, Muhammad; Nurhayati, Nurhayati (JURNAL ILMU BUDAYA, 2019)
This study aims to (1) describe the forms of the basic Indonesian sentences basic children aged 3-4 years playinggreen slope district of jeneponto and (2) describe the types of single sentences of children aged 3-4 years in the district green slope play group jeneponto. This research is a descriptive research. The approach used in this study is a syntactic approach. This research data is a sigle sentence spoken by children aged 3-4 years in the green slope play group jeneponto district. The method of reffering and proficient. The technique used in the refer and refer method is the recording technique and recording technique. The results of this study indicate that (1) forms of basic sentences based on single sentences of children aged 3-4 year in the district green slope play group jeneponto consists of  KB + KB, KB + KK, KB + KS, KB + KDep, KB + KBil, and FB + KDep and (2) types of child single sentences which consist of question words, who, when, and where the presence is at the beginning of the sentence, in the middle, and at the end sentence. As for, the question asked how and why the researchers did not find. Furthermore, the imperative sentences or command sentence consists of the commad sentence verily, prohibited sentences, and sentences invite.